Let's think about family visits in prison: a case of participatory research and committed art in Spain. (August 2021) - Ruiz-López, Julia; Saiz-Linares, Ángela; Susinos-Rada, Teresa
This paper presents a research project carried out with participatory methodology in which the collaborative creation of an audiovisual has been the driving element of a complex process of inquiry about prison reality. The objective of the project is to describe, reveal and denounce how conjugal and family visits to inmates in prison take place. We have employed artistic co-creation and media literacy as facilitators of the participation of social groups without a voice. The project is structured as a qualitative case study. The participating group consists of six men in a Centre for Social Integration, the social worker and three researchers. The results discuss the possibilities offered by art as a viable social transformative practice. Likewise, the possibilities of art as social activism and as a facilitator of new forms of knowledge accessible to all are analysed. Finally, as a device of digital artivism, the audiovisual will be disseminated.